Choosing between internal and external development for innovation projects: antecedents and consequences. Issue 1 (1st January 2017) - Ryoo, Joohan
Abstract: Unlike alliance proponents, we posited that high-tech small firms (HTSFs) may not prefer interfirm collaboration for innovation activities. Drawing on the transaction cost and corporate entrepreneurship perspectives, we proposed that boundary decisions in innovation activities are determined by the perceived uncertainties of innovation projects and entrepreneurial orientation (EO). We also examined the consequences of collaborative innovation. In a sample of 178 Korean HTSFs in software development, we found that some aspects of perceived uncertainty prevented collaborative innovation, and that EO moderated this effect, enhancing the outcomes of collaborative innovation. We discuss theoretical and practical insights of these findings.